Helminths of the broad-tailed bat Nyctinomops laticaudatus (Geoffroy Saint-Hilaire) in Mexico, and description of a new species of nematode (Molineidae: Anoplostrongylinae) - Moguel-Chin, Wilson Isaias; Suárez-Galaz, Alejandro; Casanova, Anyela Jackelin Chan-; Concha-Guillermo, Henry Orlando; Tzec-Che, Ruben Guadalupe; Robles, María Del Rosario; Digiani, María Celina; Hernández-Orts, Jesús S.; Torres, Nallely G. Ruiz; Macswiney G., M. Cristina; Panti-May, Jesús Alonso (Zootaxa, 2025)
Nyctinomops laticaudatus is an insectivorous bat distributed from Mexico to northern Argentina; however, it has few helminthological records. In the present study, we describe the helminth fauna of N. laticaudatus from the municipalities of Calcehtok and Homún in the state of Yucatán, Mexico. Helminths were identified using morphological techniques (clearing, staining, and scanning electron microscopy). We generated 28S rRNA and COI genetic sequence data for each of the taxa when possible. The helminth fauna of N. laticaudatus consisted of 17 taxa: seven trematodes, Brachylecithum rileyi, Euparadistomum sp., Limatulum nanum, Phaneropsolidae gen. sp., Ochoterenatrema sp., Urotrema minuta, and Urotrema sp.; two cestodes, Vampirolepis cf. christensoni and Vampirolepis cf. phyllostomi; six nematodes, Aonchotheca pulchra, Anoplostrongylus allami sp. nov. Panti-May & Digiani, Physaloptera sp., Physocephalus sexalatus, Spirura mexicana, and Litomosoides sp.; and two acanthocephalans, Mediorhynchus sp. and Oncicola sp. All these taxa, except for Euparadistomum sp., Mediorhynchus sp. and Oncicola sp., were recorded in both municipalities. The new species is distinguished from its only congener, Anoplostrongylus paradoxus, by the number of portions of the cephalic vesicle of males (two vs. three), the shape of the proximal half of the gubernaculum (asymmetric vs. symmetric) and, especially, by the marked sexual dimorphism in the ridge number and development. Anoplostrongylus allami had the highest prevalence and intensity values. This study adds new seven helminthological records for N. laticaudatus and four for Mexico, including the description of a new nematode species. This study also provides genetic sequences for most of the helminths found in N. laticaudatus, which will be useful in future studies, as few bat helminths have available genetic information.